(untitled) (ENTHYMEMA, 2020)
My article aims at analyising certain aspects of Claude Simon’s L’Acacia. This text is characterized by peculiar aspects and statutes that also derive from the difficulty in the interpretation of the figure of the protagonist. L’Acacia is one of the late works by Simon, it was published in 1989 and it consistently retrieves many themes and conventions of the previous texts. In fact, Simon establishes every text on a series of autobiographical and fictitious elements, that recur from one text to the other. The presence of elements linked to the author’s personal or familiar history seems to put this text in contact to the genre of the autobiography. Nonetheless, it can’t be the case of an autobiography written in third person as it appears to be paradoxical: the autobiography supposes a certain degree of complementarity between the written discourse on the page and an identity that is embodied under an I.